Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
By using carbon nanotubes and soy protein isolate in the preparation of lithium manganese phosphate materials, the problem of unevenness of iron-manganese precursors is solved through two sintering processes, the conductivity and performance of the material are improved, and suitable for industrialization Production.
Patent Information
- Application Number
- CN202411292773.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
In the existing preparation methods for lithium manganese phosphate positive electrode materials, it is difficult to synthesize a uniform iron manganese precursor, resulting in poor ion transmission rate, rate performance and cyclic reversibility of the material, which limits its commercial application.
When preparing lithium manganese iron phosphate material, carbon nanotubes and soy protein isolate are added for ultrasonic dispersion to form a carbon source, and the material forms a uniform carbon layer through two sintering processes, improving conductivity and pore structure and improving electronic conductivity .
It significantly improves the specific capacity, high rate performance and compaction density of lithium manganese iron phosphate materials, simplifies the preparation process, reduces costs and energy consumption, and is suitable for industrial production.
Smart Images

Figure BDA0005045097270000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium battery positive electrode materials, and specifically relates to a lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] The predecessor of lithium manganese iron phosphate material (LMFP) is lithium iron phosphate material (LFP). Like lithium iron phosphate active material, lithium manganese iron phosphate also has an olivine structure, in which the PO4 tetrahedron is very stable and can play a structural support role during the charge and discharge process, thus giving LMFP excellent thermodynamic and kinetic stability. In addition, because the energy density of lithium manganese iron phosphate active material is higher than that of lithium iron phosphate and the cost is lower than that of nickel cobalt manganese active material, it has become the focus of research on positive electrode active materials for lithium-ion batteries in recent years.
[0003] In the preparation process of lithium iron manganese phosphate materials, the solid phase method is widely used in the preparation of lithium iron manganese phosphate positive electrode materials because of its advantages such as simple process, less equipment required, easy production, and low cost. First, a uniform iron manganese precursor is synthesized, such as ferrous manganese oxalate, ferrous manganese phosphate, ferrous manganese phosphate, ferric manganese oxide, etc., and then it is mixed with lithium carbonate and carbon source for calcination to prepare lithium iron manganese phosphate materials. There are many studies, but the difficulty of this preparation method lies in the synthesis of uniform iron manganese precursors and the complex process flow. At the same time, the elemental heterogeneity of the iron manganese precursor affects the material's ion transfer rate, rate performance, gram capacity, and cycle reversibility, making it difficult for its capacity, rate performance, and cycle performance to meet the indicators required for actual applications, thereby restricting the commercial application process of lithium iron manganese phosphate materials.
[0004] Therefore, there is an urgent need to develop a new method for producing high-efficiency, low-cost, and high-performance lithium manganese iron phosphate positive electrode materials. Summary of the invention
[0005] The object of the present invention is to provide a lithium iron manganese phosphate positive electrode material and a preparation method and application thereof, so as to solve the problem of poor conductivity of the lithium iron manganese phosphate positive electrode material prepared by the existing method.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0008] S1, adding concentrated sulfuric acid and concentrated nitric acid to purify the carbon nanotubes, heating and reflux stirring, washing, and drying to obtain acidified carbon nanotubes; adding the acidified carbon nanotubes and soy protein isolate to a phosphate buffer solution, ultrasonically dispersing, reacting in an ice-water bath, centrifuging, filtering, and drying to obtain a carbon source;
[0009] S2, mixing the lithium source, manganese source, iron source and phosphorus source uniformly, adding the carbon source and continuing to stir uniformly, ball milling, drying, and pre-sintering to obtain a pre-sintered product;
[0010] S3. Add a carbon source to the pre-sintered product, continue ball milling, dry, and perform secondary sintering to obtain a lithium manganese iron phosphate positive electrode material.
[0011] Furthermore, in S1, the usage ratio of carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid is 50 mg: 15 mL: 5 mL; the usage ratio of acidified carbon nanotubes, soy protein isolate and phosphate buffer solution is 1-3 mg: 30 mg: 20 mL.
[0012] Furthermore, the molar ratio of lithium, manganese, iron and phosphorus elements in the lithium source, manganese source, iron source and phosphorus source added to S2 is 1:x:(1-x):1, wherein 0.4≤x≤0.6.
[0013] Furthermore, the total weight of the lithium source, manganese source, iron source and phosphorus source is recorded as A, and the weight of the carbon source added in S1 accounts for 20-25wt% of A.
[0014] Furthermore, the weight of the carbon source added to S2 accounts for 10-12 wt % of A.
[0015] Furthermore, in S2, the rotation speed of the ball mill is 400-500 r / min, and the ball milling is 3.5-4 h; the pre-sintering temperature is 350-400° C., and the sintering time is 2-3 h.
[0016] Furthermore, in S3, the rotation speed of the ball mill is 350-400 r / min, and the ball milling is 2-3 h; the secondary sintering temperature is 650-750° C., and the sintering time is 10-12 h.
[0017] Furthermore, the lithium source is at least one of lithium carbonate, lithium nitrate and lithium hydroxide; the manganese source is at least one of manganous sulfate, manganous carbonate, manganous carbonate and manganous nitrate; the iron source is at least one of ferrous oxalate, ferrous sulfate, ferrous nitrate and ferric sulfate; the phosphorus source is at least one of phosphoric acid, diammonium phosphate and ammonium phosphate.
[0018] In a second aspect, the present invention provides a lithium iron manganese phosphate positive electrode material, wherein the lithium iron manganese phosphate positive electrode material is prepared by the preparation method described in the first aspect.
[0019] In a third aspect, the present invention provides an application of the lithium iron manganese phosphate positive electrode material described in the second aspect in a lithium ion battery.
[0020] Beneficial effects of the present invention:
[0021] The present invention first adds a carbon source during the preparation of a lithium manganese iron phosphate precursor, and then pre-sinters the materials after fully mixing them at the molecular level to obtain a pre-sintered product. The pre-sintered product is then mixed with a carbon source and then secondary sintered to obtain a lithium manganese iron phosphate positive electrode material. The carbon source is added twice during the preparation process, so that the carbon layer formed by the lithium manganese iron phosphate coating has a uniform thickness and a rich pore structure, which is beneficial to the Li + The electron transfer and the formation of the conductive network effectively improve the electronic conductivity of the material. The carbon source used is prepared from soy protein isolate functionalized grafted acidified carbon nanotubes, which has good dispersibility and stability. The carbon nanotubes have a skeleton support function, which can slow down the attenuation of the material in the later stage of the cycle. At the same time, the lithium manganese iron phosphate material grows inside and outside the wall of the carbon nanotubes and can maintain the particle size of the positive electrode lithium manganese iron phosphate material, which significantly improves the specific capacity, high rate performance and compaction density of the lithium manganese iron phosphate material.
[0022] The invention provides a method for preparing a lithium manganese iron phosphate positive electrode material. The preparation method is simple, easy to control, has low energy consumption and raw material costs, high production efficiency, and can be applied to large-scale industrial production. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, and the preparation steps are as follows:
[0026] S1. 50 mg of carbon nanotubes were added to 15 mL of concentrated sulfuric acid and 5 mL of concentrated nitric acid for purification, refluxed at 80°C with stirring, washed, and dried to obtain acidified carbon nanotubes; 1.5 mg of acidified carbon nanotubes and 30 mg of soy protein isolate were added to 20 mL of phosphate buffer solution (pH = 7.2), ultrasonically dispersed, ice-bathed for 30 min, centrifuged, filtered, and dried to obtain a carbon source;
[0027] S2. According to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid are weighed, and then mixed evenly, and a carbon source is added and stirred evenly, the weight of the added lithium source accounts for 20wt% of A (the total weight of the lithium source, manganese source, iron source and phosphorus source is recorded as A), and anhydrous ethanol is used as a medium for ball milling at a speed of 420r / min for 3.5h, dried, and pre-sintered at a pre-sintering temperature of 350°C for 2.5h to obtain a pre-sintered product;
[0028] S3. Add a carbon source to the pre-sintered product, the weight of the added lithium source accounts for 10wt% of A, continue ball milling, the rotation speed is 350r / min, the ball milling is for 2.2h, dry, and perform secondary sintering at a secondary sintering temperature of 650°C and a sintering time of 11h to obtain a lithium iron manganese phosphate positive electrode material.
[0029] The lithium manganese iron phosphate positive electrode material is prepared through the above steps.
[0030] Example 2
[0031] The only difference from Example 1 is that:
[0032] S1. Add 50 mg of carbon nanotubes to 15 mL of concentrated sulfuric acid and 5 mL of concentrated nitric acid for purification, reflux with stirring at 80°C, wash, and dry to obtain acidified carbon nanotubes; add 2.8 mg of acidified carbon nanotubes and 30 mg of soy protein isolate to 20 mL of phosphate buffer solution (pH = 7.2), ultrasonically disperse, ice-bath for 30 min, centrifuge, filter, and dry to obtain a carbon source.
[0033] Example 3
[0034] The only difference from Example 1 is that:
[0035] The molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1 was replaced with the molar ratio of Li:Mn:Fe:P=1:0.5:0.5:1.
[0036] Example 4
[0037] The only difference from Example 1 is that:
[0038] S2. Lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid are weighed according to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, and then mixed evenly. A carbon source is added and stirred evenly. The weight of the added lithium source accounts for 25wt% of A. The mixture is ball-milled with anhydrous ethanol as the medium at a rotation speed of 420r / min for 3.5h. The mixture is dried and pre-sintered at a pre-sintering temperature of 350°C for 2.5h to obtain a pre-sintered product.
[0039] Example 5
[0040] The only difference from Example 1 is that:
[0041] S2. According to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid are weighed, and then mixed evenly. A carbon source is added and stirred evenly. The weight of the added lithium source accounts for 20wt% of A. Anhydrous ethanol is used as a medium for ball milling at a speed of 450r / min for 3.5h. After drying, pre-sintering is performed at a pre-sintering temperature of 400°C and a sintering time of 2h to obtain a pre-sintered product.
[0042] Example 6
[0043] The only difference from Example 1 is that:
[0044] S3. Add a carbon source to the pre-sintered product, the weight of the added lithium source accounts for 12wt% of A, continue ball milling, the rotation speed is 350r / min, the ball milling is for 2.2h, dry, and perform secondary sintering, the secondary sintering temperature is 650℃, the sintering time is 11h, and obtain lithium iron manganese phosphate positive electrode material.
[0045] Example 7
[0046] The only difference from Example 1 is that:
[0047] S3. Add a carbon source to the pre-sintered product, the weight of the added lithium source accounts for 10wt% of A, continue ball milling, the rotation speed is 400r / min, the ball milling is for 2h, and then dry, and perform secondary sintering at a secondary sintering temperature of 700°C and a sintering time of 12h to obtain a lithium iron manganese phosphate positive electrode material.
[0048] Comparative Example 1
[0049] This comparative example provides a method for preparing a lithium manganese iron phosphate positive electrode material, and the preparation steps are as follows:
[0050] S1. Lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid were weighed according to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, and then mixed evenly, and ball-milled with anhydrous ethanol as a medium at a speed of 420 r / min for 3.5 h, dried, and pre-sintered at a pre-sintering temperature of 350°C for 2.5 h to obtain a pre-sintered product;
[0051] S2. The pre-sintered product is further ball-milled at a rotation speed of 350 r / min for 2.2 h, dried, and subjected to secondary sintering at a secondary sintering temperature of 650° C. for 11 h to obtain a lithium manganese iron phosphate positive electrode material.
[0052] The lithium manganese iron phosphate positive electrode material is prepared through the above steps.
[0053] Comparative Example 2
[0054] The only difference from Example 1 is that:
[0055] S2. According to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid are weighed, and then mixed evenly, and a carbon source is added and stirred evenly, the weight of the added lithium source accounts for 30wt% of A, and anhydrous ethanol is used as a medium for ball milling at a speed of 420r / min for 3.5h, dried, and pre-sintered at a pre-sintering temperature of 350°C for a sintering time of 2.5h to obtain a pre-sintered product;
[0056] S3. The pre-sintered product is further ball-milled at a rotation speed of 350 r / min for 2.2 h, dried, and subjected to secondary sintering at a secondary sintering temperature of 650° C. for 11 h to obtain a lithium manganese iron phosphate positive electrode material.
[0057] Comparative Example 3
[0058] The only difference from Example 1 is that:
[0059] S2. Lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid were weighed according to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, and then mixed evenly, and ball-milled with anhydrous ethanol as the medium at a speed of 420 r / min for 3.5 h, dried, and pre-sintered at a pre-sintering temperature of 350°C for 2.5 h to obtain a pre-sintered product;
[0060] S3. Add a carbon source to the pre-sintered product, the weight of the added lithium source accounts for 30wt% of A, continue ball milling, the rotation speed is 350r / min, the ball milling is 2.2h, dry, and perform secondary sintering. The secondary sintering temperature is 650°C and the sintering time is 11h to obtain a lithium iron manganese phosphate positive electrode material.
[0061] Comparative Example 4
[0062] The only difference from Example 1 is that:
[0063] S2. According to the molar ratio of Li:Mn:Fe:P=1:0.4:0.6:1, lithium carbonate, manganous sulfate, ferrous oxalate and phosphoric acid are weighed, and then mixed evenly. A carbon source is added and stirred evenly. The weight of the added lithium source accounts for 20wt% of A. Anhydrous ethanol is used as a medium for ball milling at a speed of 300r / min for 3h. After drying, pre-sintering is performed at a pre-sintering temperature of 300°C and a sintering time of 2h to obtain a pre-sintered product.
[0064] Comparative Example 5
[0065] The only difference from Example 1 is that:
[0066] S3. Add a carbon source to the pre-sintered product, the weight of the added lithium source accounts for 10wt% of A, continue ball milling, the rotation speed is 500r / min, the ball milling is 2.2h, dry, and perform secondary sintering. The secondary sintering temperature is 550°C and the sintering time is 11h to obtain a lithium iron manganese phosphate positive electrode material.
[0067] Examples 1 to 7 and Comparative Examples 1 to 5 were applied and tested:
[0068] The lithium manganese iron phosphate positive electrode material obtained in the embodiment and the comparative example was used as the positive electrode material. The positive electrode material: SP (superconducting carbon black): PVDF (polyvinylidene fluoride) were slurried at a mass ratio of 90:5:5 and coated on a 20 μm thick aluminum foil to prepare a positive electrode sheet with a surface density of 8 mg / cm 2 , and then through drying, rolling, die cutting, punching into positive electrode sheets. Use R2032 button battery shell for button battery assembly, use lithium sheet as negative electrode, use PE material diaphragm, and drip 80μmL of electrolyte (the electrolyte uses Xinzhoubang lithium-ion battery electrolyte, model LBC3401A60).
[0069] The electrochemical performance of the battery prepared above was tested:
[0070] The 1C cycle performance test was carried out at 25°C, and the button battery prepared above was tested using a blue electric tester: the prepared button battery was placed in a high-temperature oven at 25°C for charge and discharge test, the voltage range was 2.0V-4.35V, 0.1C charge and discharge activation for one cycle, and then charged at 0.5C constant current and constant voltage, the cut-off current was 0.05C, and constant current discharge was carried out at 1C current, and 50 cycles were cycled to obtain the relevant data of parameters such as the first discharge specific capacity and the 50th cycle capacity retention rate; the test results are shown in Table 1:
[0071] Table 1
[0072]
[0073] It can be seen from Table 1 that, compared with Comparative Examples 1-5, the lithium iron manganese phosphate positive electrode material prepared in Examples 1-7 has good electrochemical performance, high capacity retention rate, better cycle performance, and better compaction density. It can be seen that the preparation method of the lithium iron manganese phosphate positive electrode material provided by the present invention can significantly improve the specific capacity, high rate performance and compaction density of the lithium iron manganese phosphate positive electrode material.
[0074] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: S1, adding concentrated sulfuric acid and concentrated nitric acid to purify the carbon nanotubes, heating and reflux stirring, washing, and drying to obtain acidified carbon nanotubes; adding the acidified carbon nanotubes and soy protein isolate to a phosphate buffer solution, ultrasonically dispersing, reacting in an ice-water bath, centrifuging, filtering, and drying to obtain a carbon source; S2, mixing the lithium source, manganese source, iron source and phosphorus source uniformly, adding the carbon source and continuing to stir uniformly, ball milling, drying, and pre-sintering to obtain a pre-sintered product; S3. Add a carbon source to the pre-sintered product, continue ball milling, dry, and perform secondary sintering to obtain a lithium manganese iron phosphate positive electrode material.
2. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In S1, the usage ratio of carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid is 50 mg: 15 mL: 5 mL; the usage ratio of acidified carbon nanotubes, soy protein isolate and phosphate buffer solution is 1-3 mg: 30 mg: 20 mL.
3. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The molar ratio of lithium, manganese, iron and phosphorus elements in the lithium source, manganese source, iron source and phosphorus source added to S2 is 1:x:(1-x):1, wherein 0.4≤x≤0.
6.
4. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The total weight of the lithium source, manganese source, iron source and phosphorus source is recorded as A, and the weight of the carbon source added in S1 accounts for 20-25wt% of A.
5. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The weight of the carbon source added to S2 accounts for 10-12 wt% of A.
6. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In S2, the rotation speed of the ball mill is 400-500r / min, and the ball milling is 3.5-4h; the pre-sintering temperature is 350-400℃, and the sintering time is 2-3h.
7. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The speed of ball milling in S3 is 350-400r / min, and the ball milling is 2-3h; the secondary sintering temperature is 650-750℃, and the sintering time is 10-12h.
8. The method for preparing a lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The lithium source is at least one of lithium carbonate, lithium nitrate and lithium hydroxide; the manganese source is at least one of manganous sulfate, manganous carbonate, manganous carbonate and manganous nitrate; the iron source is at least one of ferrous oxalate, ferrous sulfate, ferrous nitrate and ferric sulfate; the phosphorus source is at least one of phosphoric acid, diammonium phosphate and ammonium phosphate.
9. A lithium manganese iron phosphate positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. An application of a lithium iron manganese phosphate positive electrode material, wherein the lithium iron manganese phosphate positive electrode material is applied to a lithium ion battery, and the lithium iron manganese phosphate positive electrode material is the lithium iron phosphate material as claimed in claim 9.
Citation Information
Patent Citations
Lithium manganese phosphate-three-dimensional carbon skeleton composite positive electrode material and preparation method thereof
CN107689448A
Method for using isolated soybean protein to functionally modify single-walled carbon nanotube
CN108285136A
Preparation method of lithium iron manganese phosphate serving as anode material of lithium ion battery
CN114665058A
Lithium manganese iron phosphate composite material and preparation method thereof
CN117558883A
Lithium manganese iron phosphate material as well as preparation method and application thereof
CN118289723A
Cited By
Modified positive electrode material, preparation method thereof and lithium ion battery
CN121591188A
Preparation method of lithium iron phosphate anode material with super-long cycle life
CN122831310A
